Mechanism Enhancing Arabidopsis Resistance to Cadmium: The Role of NRT1.5 and Proton Pump - Wang, Tao; Hua, Yingpeng; Chen, Moxian; Zhang, Jianhua; Guan, Chunyun; Zhang, Zhenhua (Frontiers in Plant Science, 2018)
Aims Heavy metal pollution is serious in China, and abscisic acid (ABA) is an important stress hormone.How it regulates plant tolerance to cadmium remains unclear, so we aimed to explore the molecular mechanism responsible for enhanced cadmium resistance in Arabidopsis wild-type and mutant plants and Brassica napus seedlings. Methods Arabidopsis/B. napus were cultured hydroponically for 28/15 days and then treated with 20/10 µM Cd/Cd+ABA (5 M) for 3/4 days. Chlorophyll degradation rate, SPAD values, proline, MDA, ABA, NO3-, and Cd concentrations were measured in root vacuoles and protoplasts; root to shoot NO3- and Cd concentration ratios were determined and NRT1.5-, NRT1.8-, BnNRT1.5- and BnNRT1.8-related gene expression was studied. Results Cytoplasmic ABA levels in root cells of bglu10 and bglu18 Arabidopsis mutants were significantly lower than those in the wild-type, apparently making the latter more resistant to Cd. NO3- long-distance transporter NRT1.5 responded to ABA signaling by downregulating its own expression, while NRT1.8 did not respond. Concomitantly, proton pump activity in wild-type plants was higher than in the bglu10 and bglu18 mutants; thus, more NO3- and Cd accumulated in the vacuoles of wild-type root cells. ABA application inhibited Cd absorption by B. napus. BnNRT1.5 responded to exogenous ABA signal by downregulating its own expression, while the lack of response by BnNRT1.8 resulted in increased amount of NO3- accumulating in the roots to participate in the anti-cadmium reaction. Conclusions NRT1.5 responds to the ABA signal to inhibit its own expression, whereas unresponsiveness of NRT1.8 causes accumulation of NO3- in the roots; thus, enhancing Cd resistance. In Arabidopsis, because of proton pump action, more NO3- and Cd accumulate in the vacuoles of Arabidopsis root cells, thereby reducing damage by Cd toxicity. However, in B. napus, the addition of exogenous ABA inhibited Cd absorption. Our data provide a sound basis to the theoretical molecular mechanism involved in hormone signaling during response of plants to heavy metal stress.